Analisis Pengaruh Faktor Fundamental terhadap Return Saham - Hariyani, Diyah Santi; Setiyono, Wahyu; Langgeng. W, Anggita; Apriyanti, Apriyanti (Universitas Swadaya Gunung Jati, 2018)
Purpose this study to test empirically the influence of fundamental factors on Stock Return. Quantitative research, with purposive sampling method of property and real estate sector companies listed on the Indonesia Stock Exchange in 2014-2016 using the quarterly period. which meets the criteria has been selected as a sample of 23 companies to analyze data by techniques used in this study are multiple regression and hypothesis testing using t-test and F-test with a significant level of 5%. results of this research show that only partially Interest Rate that significantly influence the Return of Share, while the Current Ratio (CR), Total Asset Turn Over (TATO), Debt To Equity Ratio (DER), Net Profit Margin (NPM) and Inflation is not significant effect on Stock Return. While simultaneously Current Ratio (CR), Total Asset Turn Over (TATO), Debt To Equity Ratio (DER), Net Profit Margin (NPM), Interest Rate and Inflation significantly influence Stock Return.Keywords: Fundamental Factors, Stock Return.